SISTEM HUKUM BARAT, SISTEM HUKUM ADAT, DAN SISTEM HUKUM ISLAM, MENUJU SEBAGAI SISTEM HUKUM NASIONAL SEBUAH IDE YANG HARMONI - H Mustaghfirin (Jurnal Dinamika Hukum, 2011)
West Legal System follow the philosophy of legal positivism values conflict with the noble values of the Indonesian nation, so there Gab between the law and people of Indonesia are regulated, System of Customary Law in the values of certain indigenous communities whose territory reached 350 indigenous territories, and can only be believed by public socialized habits, and can not be validated as a national law, and Islam as the Legal System is based on the attributes of God as "Asmaul Husna" and diamalkan believed by the majority of individuals nationwide Indonesian society and tolerance of permanent values believed by minority groups in Indonesia, therefore the system of Islamic law that allows a system of national law in accordance with the personality of the Indonesian nation and not betentangan with the values of Pancasila. Keywords   :  Western Legal System, system of customary law, islamic legal system, the national legal system, perspective of legal philosophy, harmony.